Model of formation of readiness for positive interaction of educational space actors in a substitute family - Lyudmila Alexandrovna Saenko; Galina Nicolaevna Solomatina (Вестник Майкопского государственного технологического университета)
The article presents aspects of the concept of readiness for positive interaction between the subjects of the educational space of a substitute family. The article analyzes the views of researchers on the concept of “willingness to interact.” The structure of readiness for positive interaction, including motivational personality, cognitive and operational-effective components, is presented. The content of each of the structural components of readiness is presented. The article presents a detailed analysis of the subjects of an educational space: 1) parents, aimed at creating a foster (substitute) family; 2) orphans raised in boarding schools; 3) specialists working with substitute families. Considerable attention is paid to the model of formation of readiness for the positive interaction of subjects. The structure of the model combines the target, organizational, informative and effective blocks. Considerable attention is paid to the content and description of each block. The integration of the content of the marked blocks is aimed at the effectiveness of the model implementation. Special attention is paid to effective and inefficient interaction in a foster family. Reasons have been highlighted, characteristics have been given. Practical experience of testing the model of readiness for positive interaction between the subjects of the educational space of a foster family. The results of the study on the testing of a model based on an educational institution engaged in the targeted preparation of subjects of an educational space of a substitute family (for example, training of teachers, psychologists and other specialists working with substitute families) are presented.